New Record of Diversity and Distribution Pattern of Local Butterfly in Ternate Island - Abdu Mas'ud; Wawan Hariswan; Sundari Sundari; M. Nasir Tamalene (Jurnal Biologi Tropis, 2022)
Ternate is one of the spots in the Walacea expedition. Ternate Island has unique characteristics in the diversity of flora and fauna. So far, information on local butterfly diversity has not been reported. The purpose of this study is to update the latest information on the diversity and distribution pattern of local butterfly species on the island of Ternate for conservation efforts. An exploratory descriptive research using survey method has been conducted at the research location on the island of Central Ternate. The results of the study found 88 individuals consisting of 15 types of local butterflies from 5 families, namely; 1) family Papilionidae as many as 2 species including Pachliopta polyphontes, Papilio sataspes; 2) the Nymphalidae family as many as 9 species including Euploea tulliolus, Danaus genutia, Mycalesis perseus caesonia, Paratica Aspasia-aspasia, Limenitis helena, Yoma sabina, Vindula dejone dorokusana, Ideopsis similis, Cyrestis acilia latifascia; 3) family Pieridae as many as 2 types Pieris brassicae, Eurema sari sodalis); 4) 1 species of Lycaenidae family (Arhopala major) and 5) 1 species of Callidulidae family (Callidula evander). The local butterfly diversity index value on the island of Central Ternate is H'= 2.33 categorized as low diversity. Furthermore, the analysis of the distribution pattern is 17.6 or S2 > x̄, categorized as group distribution.